Erythropoietin attenuates pulmonary vascular remodeling in experimental pulmonary arterial hypertension through interplay between endothelial progenitor cells and heme-oxygenase - Rosa L.E. Loon; Beatrijs eBartelds; Beatrijs eBartelds; Frank A.D.T.G. Wagener; Nada eAffara; Saffloer eMohaupt; Hans eWijnberg; Sebastiaan W.C. Pennings; Janny eTakens; Rolf M.F. Berger; Rolf M.F. Berger (Frontiers Media S.A., 2015)
BackgroundPulmonary arterial hypertension (PAH) is a pulmonary vascular disease with a high mortality, characterized by typical angio-proliferative lesions. Erythropoietin (EPO) attenuates pulmonary vascular remodeling in PAH. We postulated that EPO acts through mobilization of endothelial progenitor cells (EPCs) and activation of the cytoprotective enzyme heme oxygenase-1 (HO1).MethodsRats with flow-associated PAH, resembling pediatric PAH, were treated with HO-1 inducer EPO in the presence or absence of the selective HO-activity-inhibitor tin-mesoporphyrin (SnMP). HO-activity, circulating EPCs and pulmonary vascular lesions were assessed after 3 weeks.ResultsIn PAH-rats, circulating EPCs were decreased and HO-activity was increased compared to control. EPO-treatment restored circulating EPCs and improved pulmonary vascular remodeling, as shown by a reduced wall thickness and occlusion rate of the intra-acinar vessels. Inhibition of HO-activity with SnMP aggravated PAH. Moreover, SnMP treatment abrogated EPO-induced amelioration of pulmonary vascular remodeling, while surprisingly further increasing circulating EPCs as compared with EPO alone.ConclusionsIn experimental PAH, EPO treatment restored the number of circulating EPC's to control level, improved pulmonary vascular remodeling, and showed important interplay with HO-activity. Inhibition of increased HO-activity in PAH-rats exacerbated progression of pulmonary vascular remodeling, despite the presence of restored numbers of circulating EPC's. We suggest that both EPO-induced HO1 and EPCs are promising targets to ameliorate the pulmonary vasculature in PAH.